(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Telematic transport system (TTS) - automatic collection, processing, transmission and request of information about the location and condition of vehicles, information obtained on the basis of data for efficient and safe use of vehicles for various purposes. an information system that provides provision to consumers. goals and objects. Intelligent transport system (ITS) is a telematic transport system that provides the implementation of very complex functions for processing information and developing optimal solutions and management actions. Until now, there is no single opinion about what intelligent transport systems are. In modern conditions, the central problem of efficient organization of the transport process in many large cities and non-urban sections of the road network with heavy traffic is the optimization of the use of limited public resources road network